A political companion to W.E.B. Du Bois - Bromell, Nicholas Knowles (University Press of Kentucky, 2018)
W.E.B. Du Bois was not a liberal, Marxist, radical, or republican-he was all of these and none. In 'A Political Companion to W.E.B. Du Bois', Nick Bromell assembles essays from both new and established scholars from a variety of disciplines to explore Du Bois's contributions to American political thought. The contributors establish a conceptual context within which to read the author, revealing how richly and variously he engaged with the aesthetic and theological modalities of political thinking and action. This volume further reveals how Du Bois's work challenges and revises contemporary political theory, providing commentary on the author's strengths and limitations as a theorist for the twenty-first century.
Keywords: Du Bois, W. E. B. -- (William Edward Burghardt), -- 1868-1963 -- Political and social views.; Du Bois, W. E. B. -- (William Edward Burghardt), -- 1868-1963 -- Criticism and interpretation.; Du Bois, W. E. B. -- (William Edward Burghardt), -- 1868-1963; Du Bois, William E. B. -- 1868-1963; African Americans -- Politics and government -- Philosophy.; Politics and literature -- United States -- History -- 20th century.; Noirs américains -- Politique et gouvernement -- Philosophie.; Politique et littérature -- États-Unis -- Histoire -- 20e siècle.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; LITERARY CRITICISM -- American -- African American.; Political and social views; Politics and literature; United States; Politisches Denken; 1900-1999; Criticism, interpretation, etc.; History